Socio-economic rights, political action, judicial conceptions of democracy and transformation : South Africa and Nigeria - Brand, Danie (Jacobus Frederick Daniel, 1968- ) (University of Pretoria, 2015)
Thesis (LLD)--University of Pretoria, 2014.